Petrography, mineralogy and geochemistry of the chert nodules in the Middle-Late Eocene Pila Spi Formation, High Folded Zone, Northern Iraq - Ali, Zubaida Z.; Asaad, Irfan Sh; Al-Juboury, Ali I.; Akkoca, Dicle Bal (Pergamon-Elsevier Science Ltd, 2026)
Chert nodules in the Middle-Late Eocene Pila Spi Formation are subjected to petrographic, mineralogical and geochemical analyses to clarify their source, growth factors and mechanism of their formation. Four types of silica are recognized: opal-silica, microcrystalline quartz, macrocrystalline quartz, and chalcedony. While, their host rocks consist dominantly of several shallow marine skeletal grains in dolomitized mudstone and wackestone microfacies. In the chert samples, quartz predominates, with small amounts of dolomite and feldspar, hematite, and calcite; in the host rocks, dolomite predominates, with smaller amounts of calcite, quartz, and illite. Scanning electron microscopy (SEM) examinations shows that chert is common with quartz grains of dominantly subhedral and sub angular microcrystalline forms. While dolomite rhombs, calcite grains, sparry calcite and radial fibrous calcite cement, and diagenetic illite clay mineral characterized the host rock samples. Major oxides in the chert nodules are dominated by SiO2, followed by CaO, MgO and Fe2O3. In the host rocks, CaO is the dominant followed by MgO and SiO2. The distribution of rare earth elements (REE) and key geochemical parameters, such as Ce/Ce*, Eu/Eu*, and TREE, is evident among different chert samples with variation between moderate negative cerium and positive europium anomalies. The silica in the studied nodular cherts was derived from biogenic, detrital, and diagenetic sources. Geochemical proxies support deposition under marine, dysoxic to anoxic conditions with limited terrigenous input. Rare earth element patterns and redox indicators suggest initial oxic deposition modified later by early diagenetic fluids.
Keywords: Chert nodules; Eocene; Biogenic input; REE; SEM; Oxic conditions